MENINGKATKAN MOTIVASI DAN MINAT BELAJAR SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN LEMBAR KERJA KOMPETENSI DASAR MENYUSUN LAPORAN KEUANGAN MATA PELAJARAN AKUNTANSI KELAS XI/B AKUNTANSI DI SMK NEGERI 1 BARABAI TAHUN AJARAN 2013/2014 - Waras Budi Purwanto (JURNAL SOCIUS, 2014)
The Purpose of  this research is to describe the students motivation and  the study response of  XI/B-AK to lesson of accounting which can be improved by using student teams achievement division (STAD) as teaching strategy. The approach which used on this classroom action research is qualitative analysis, which emphasizes on the research problem especially in improving the motivation and the study response in accounting. Therefore, the problem can be identified and analyzed then found alternative solutions. The results of the research shows that: (1) the students motivation on improved, (2) the study response on improved while  using STAD. Key Words: Motivation, study response, STAD and accounting.